Induction of NQO1 and Neuroprotection by a Novel Compound KMS04014 in Parkinson's Disease Models - Son, Hyo Jin; Choi, Ji Hyun; Lee, Ji Ae; Kim, Dong Jin; Shin, Kye Jung; Hwang, Onyou (HUMANA PRESS INC, 2015)
Parkinson's disease (PD) is a progressive neurodegenerative disorder associated with a selective loss of the neurons containing dopamine (DA) in the substantia nigra pars compacta. Lines of evidence suggest that oxidative stress is a major factor contributing to the vulnerability of DA cells and that the enzyme NAD(P) H quinone oxidoreductase (NQO1) provides protection in these cells. In the present study, we report the synthesis of a novel compound KMS04014 and show that it induces NQO1 gene expression and protects DAergic neuronal cells in both cell culture and animal models of PD. In vitro, KMS04014 increased both mRNA and protein levels of NQO1 and induced nuclear translocation of Nrf2 in the DAergic neuronal cell line CATH. a. It also protected the cells against oxidative stress generated by tetrahydrobiopterin, 1-methyl-4-phenylpyridinium (MPP+), and H2O2. In vivo, KMS04014 attenuated the loss of tyrosine hydroxylase-immunopositive DAergic neurons in the substantia nigra and reduced degeneration of the nigral neurons and striatal fibers in 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-treated mice, an animal model of PD. Taken together, KMS04014 may be utilized toward development of neuroprotective therapy for PD.
Keywords: DOPAMINERGIC-NEURONS; OXIDATIVE STRESS; SH-SY5Y CELLS; NAD(P)H-QUINONE OXIDOREDUCTASE-1; CYCLOOXYGENASE-2 EXPRESSION; PROTEASOMAL DEGRADATION; NEUROBLASTOMA-CELLS; QUINONE FORMATION; POTENTIAL ROLE; DT-DIAPHORASE